Judicial control of administrative decisions in Islamic shariah and law: الرقابة القضائية على القرارات الإدارية في الشريعة والقانون - Alzaabi, Ahmed Abdulaziz; Marni, Nurazmallail (al-Irsyad: Journal of Islamic and Contemporary Issues, 2018)
Judicial supervision or the Ombudsman’s mandate in Islamic legislation is an important guarantee of justice. It was created by the need for a deviation in the use of powers by some officials and high-ranking authorities in the state. This decision will be applied if harm is caused to a person by the decision of the authority. It can be applied by challenging the decision of the administration in the concerned courts or what was known as the resort to the Ombudsman in the Islamic era. This study aims also to identify the injustices in the Islamic era in terms of origin, evidence of the legality of dismissal in People’s grievances, conditions of the appointment. The Ombudsperson and the powers of the Ombudsperson, and then sheds the light on the system of judicial control over administrative decisions in terms of definition, characteristics, advantages, jurisdictions, and methods of judicial control and its manifestations and guarantees. In order to reach the results and recommendations through a scientific methodology to study using the analytical, historical, and comparative method.